Camera, Set, Action: Process Innovation for Film and TV Production - Ouyang Chun; Wang Kenneth; Hofstede Arthur ter; Rosa Marcello La; Rosemann Michael; Shortland Katherine; Court David (Cultural Science)
Film and TV productions, a key area in production screen business, comprise of processes with high demand for creativity and flexibility. However, despite the era of fast developing technology, film production processes are carried out in an old fashioned way. This is reflected, for example, by the fact that document processing accompanied by daily shooting activities is still primarily paper-based and coordinating geographically distributed cast and crew is purely manual or at best through emails. There is an opportunity to bring process innovation into this industry, which can streamline and optimise film production processes and thus reduce production costs.